PENINGKATAN HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIK DAN DINAMIK MELALUI STRATEGI BERFIKIR KRITIS DENGAN MODEL FLEX YOUR BRAIN (Studi kasus di SMA NEGERI 3 BANDA ACEH) - Sri Suryawati (JURNAL FISIKA EDUKASI, 2014)
This research purpose is to determine significant differences student mastery of the material fluid static and dynamic teacher who taught using flex your brain by not using flex your brain. The population in this study were all students of class XI IA SMA 3 Banda Aceh consists of 6 classes numbered 188 academic year 2013/2014, a sample of which is a class XI IA by two classes totaling 54 people. The sampling technique used was purposive sampling . Analysis of the data using the formula t-test at significance level of 5%. Based on the analysis of the results obtained by t-test = 3.69 and t-table = 1.68. This suggests that there are significant differences student mastery of the material fluid static and dynamic teacher who taught using flex your brain by not using flex your brain in class XI IA SMAN 3 Banda Aceh.